GEOTECHNICAL ASPECTS OF THE DESIGN AND BEHAVIOUR OF THE HIGHWAY BRIDGE OVER DRADER RIVER IN MAROCCO - J. P. Magnan; H. Ejjaaouani; M. Virollet; A. Tahour (International Association of Lowland Technology, 2000)
The motorway bridge on the Drader River suffered from severe floods, which occurred during its construction in 1995-1996. At this site, 8 m thick compressible soft clays layers were found during the site investigations and piled abutments were designed. During the flood, due to erosion of the riverbed under the bridge, the piled abutments were displaced and came in contact with the bridge deck. The access embankments were taken away and a new project was established for the abutments and embankments. L-shaped retaining walls prevent any contact between the fill and the abutments and hollow concrete tubes were placed in the fill in order to reduce the load applied to the ground surface.